MODELING VERTICAL MOBILITY OF P IN REGOSOLS OF THE BRAZILIAN SEMIARID REGION: LEACH COLUMN EXPERIMENT - Alves Carneiro, Kalline de Almeida; Fraga, Vânia da Silva; Correa, Marcus Metri; Dantas Antonino, Antônio Celso; da Silva, Lívia Previatello; Moro, Letícia; Salgueiro Gondim, Manuella Virginia; Dias, Bruno de Oliveira; Vargas de Mello, Jaime Wilson; Macedo, Rodrigo Santana; u. a. (Revista Valore, 2023)
Phosphorus (P) mobility can be high in sandy soils in tropical regions due to its high proportion of macropores, low levels of Fe and/or Al oxides, and low natural levels of organic matter. The aim of this study was to verify if the fit with convection-dispersion model (CDE) is adequate to analyze P vertical mobility in Regosols from the Brazilian semiarid region. Leaching columns were packed with two soils, fertilized with cattle manure. The columns were prepared based on the hydrodispersive parameters of the modeling with potassium bromide (KBr) and saturated flow. Soil samples were saturated with calcium chloride (CaCl2) and potassium chloride (KCl), both 0.001 mol L-1, and a pulse of 0.6 mmol L-1 of P. The hydrodispersive parameters (inverse method) were estimated using the CDE (CXTFIT). The soil samples packed in the columns, the delay factors (R) were around 1, the dispersivity values (λ) were very close, and the Péclet numbers (Pe) were greater than 10. In the P pulse transport assay, Pleached contents were on average 270.8 mg L-1, and it was observed that most of Pleached were translocated with 20 Vp, from 40 Vp the relationship between concentration and volume remains constant; hydrodynamic dispersion coefficients (D) ranged from 22.85 to 72.50 cm2 h-1, R ranged from 2.36 to 5.23, Damkohler number (ω) values were less than 1, and Pe ranged from 0.76 to 2.40. The adjustment with the CDE was efficient to demonstrate the vertical mobility of P in Regosols of the Brazilian semiarid region.